Hymns of Repentance - St. Romanos the Melodist; Andrew Mellas (New York, USA St. Vladimir's Seminary Press, 2020)
"This is a new translation of the Lenten kontakia of Saint Romanos the Melodist of Constantinople (AD c. 490-c. 556). He was a master poet and hymnographer, who synthesized Greco-Roman rhetoric and poetry and Greek (especially Cappadocian) patristic theology and themes with Syriac poetic and theological sensibilities. This series of kontakia was sung in Great Lent in Constantinople, and follows the liturgical commemorations of those weeks (largely unchanged to the present day)"--
Keywords: Patristics (3Yde GdBHGFjGJs; History; Patrology